Patient-centred infertility care: a scoping review protocol. Issue 11 (14th November 2019) - Webair, Hana Hasan; Ismail, Tengku Alina Tengku; Ismail, Shaiful Bahari; Mohd Noor, Norhayati
Abstract : Introduction: Patient-centred infertility care (PCIC) is one of the quality indicators of effective fertility care. The application of this indicator requires a clear definition from the patient's perspective. This proposed scoping review aims to explore the extent and nature of published scientific literature on PCIC in the past decade, identify gaps in the literature and define PCIC from infertile patients' perspectives. Methods and analysis: We will conduct the proposed scoping review following the method of Arksey and O'Malley. The literature search will include studies published from 2009 to 2019, and will be conducted on the MEDLINE, PsycINFO, Scopus, Cochrane Library, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases; reference lists will be mined for literature not contained on these databases. A grey literature search will also be conducted. To be included in the review, studies should have been conducted on people with a history of infertility, with a focus on patient-centred fertility care. Studies that have not been published in full text and studies published in languages other than English will be excluded. After study selection, data will be charted in a prepared form. We will analyse the data using descriptive numerical and qualitative thematic analyses to answer the research questions. NVivo V.12 will be used for data extraction. Ethics and dissemination: This work does not warrant any ethical or safety concerns. This scoping review will synthesise existing literature on PCIC, and the results will be published to be readily available for clinical audiences and policymakers. These findings may support clinicians and decision-makers in applying PCIC, thereby promoting high-quality healthcare in the concerned population.